2018
DOI: 10.21608/ejcm.2018.22994
|View full text |Cite
|
Sign up to set email alerts
|

Attention Deficit Hyperactivity Disorder in A Rural Area of Sohag Governorate

Abstract: Background: Attention deficit hyperactivity disorder (ADHD) is a rising public health problem affecting child quality of life. Objectives: To estimate the prevalence and identify socio-demographic risk factors of attention deficit hyperactivity disorder (ADHD) among primary school children in a rural area of Sohag governorate. Methods: A crosssectional community based study design was carried out in two villages of Sohag governorate using structured interview questionnaire. To identify children with probable A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
4
1
Order By: Relevance
“…This finding is inconsistent with the work of [10] who showed a higher proportion of ADHD among urban resident than rural resident children.…”
Section: Discussioncontrasting
confidence: 98%
“…This finding is inconsistent with the work of [10] who showed a higher proportion of ADHD among urban resident than rural resident children.…”
Section: Discussioncontrasting
confidence: 98%
“…This is accordance with several studies that showed a wide range of prevalence rates between 2% and 17% (9) . In Arab countries the reported rate was between (1.3% -34.5%), the worldwide prevalence rate of ADHD was 5.3% (4) . This consisted with the present study finding.…”
Section: Discussionmentioning
confidence: 97%
“…The reported rate in this study is a little lower than that reported by studies conducted in Egypt they reported that prevalence of ADHD 6.5% among 4223 school age children (10) , other study conducted in El-Minia city found that prevalence of ADHD were 6.9% among 1362 elementary school students (11) , and other study in (2014) found that 87(9.4%) students had a potential ADHD diagnosis among 925 student (12) , EL-Gendy et al conducted study in Al-Qalyubia Governorate in Egypt by they found that prevalence of ADHD was 21.8% based on the teacher's rating scale and 16.2% based on the parent's rating scale (13) , and study conducted in Sohag Governorate in Egypt by Ahmed in 2018 who found that prevalence rate of ADHD were 9.6% (4) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers from Egypt also reported associations between ADHD and factors like a low socioeconomic level, higher birth order, male gender, smoker fathers, consanguineous parents, family history of ADHD, low birth weight, artificially fed children, and pupils living with a single parent. (10,11) Other factors that have been found to have an association with ADHD include watching TV, cyanosis, and head trauma, being male, living with a single parent, childbirth order/rank, and low family socioeconomic status. (12) The current study revealed that the proportion of ADHD among primary school student was (14.2%).This agree with Adnan H in 2020 in Iraq-Hilla city revealed that the overall prevalence of ADHD in the study group was 14%.…”
Section: Discussionmentioning
confidence: 99%